Indian Research Universities and Global Rankings - Jalote, Pankaj (International Higher Education, 2019)
There is a strong desire, in countries like India, to see some of the best national research institutions recognized among top universities globally. In this article, we show that the age, size, and funding profile of top Indian institutions is radically different from that of the top 200 global universities. Top global universities are generally old, large in size, and well-funded—while Indian institutions are generally quite young, small in size, and have modest funding. The article suggests that top Indian universities might make it to global rankings if the two parameters that are in control—size and funding—are aligned to the global pattern.